The Effects of a Digital Articulatory Game on the Ability to Perceive Speech-Sound Contrasts in Another Language - Ylinen, Sari; Smolander, Anna-Riikka; Karhila, Reima; Kakouros, Sofoklis; Lipsanen, Jari; Huotilainen, Minna; Kurimo, Mikko (Frontiers in Education, 2021)
Digital and mobile devices enable easy access to applications for the learning of foreign languages. However, experimental studies on the effectiveness of these applications are scarce. Moreover, it is not understood whether the effects of speech and language training generalize to features that are not trained. To this end, we conducted a four-week intervention that focused on articulatory training and learning of English words in 6-7-year-old Finnish-speaking children who used a digital language-learning game app Pop2talk. An essential part of the app is automatic speech recognition that enables assessing children’s utterances and giving instant feedback to the players. The generalization of the effects of such training in English were explored by using discrimination tasks before and after training (or the same period of time in a control group). The stimuli of the discrimination tasks represented phonetic contrasts from two non-trained languages, including Russian sibilant consonants and Mandarin tones. We found some improvement with the Russian sibilant contrast but it was not statistically significant. No improvement was observed for the tone contrast for the gaming group. A control group with no training showed no improvement in either contrast. The pattern of results suggests that the game may have improved the perception of non-trained speech sounds in some but not all individuals, yet the effects of motivation and attention span on their performance could not be excluded with the current methods. Children’s perceptual skills were linked to their word learning in the control group but not in the gaming group where recurrent exposure enabled learning also for children with poorer perceptual skills. Together, the results demonstrate beneficial effects of learning via a digital application, yet raise a need for further research of individual differences in learning.